PROTECTION AGAINST THE LAW OF LAND RIGHTS IN PROCUREMENT AND CANCELLATION RIGHTS LAND FOR PUBLIC INTEREST - ., Arba; Rahman, Arief; Wahyuningsih, Wiwiek; Andriyani, Shinta (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
This research aims to study and understand the legal principles of legal protection arrangements rights of individuals and communities in the provision of land for the development of means of general interest based on Act No. 20 of 1961 and Act No. 2 of 2012.These research is normative law, therefore the method of approach is useful to review the normative foundations, norms, concepts of the law written in the legislation. The approach is the approach of the legislation, the concept approach, analytical approach, and comparative approach.The results after analysis showed that: a good provision of land for the development of means of general interest based on Act Number 20 of 1961 as well as based on Act Number 2 of 2012 while providing legal protection high on the right. This is reflected in the various provisions of the law are decanted in the second law. More over even provide the same legal protection, but between this law there are similarities and differences of laws principles and the legal process in the implementation